Iceland Competitions (project baikal, 2020)
Bee Breeders is introducing its first country-based architecture competition series, with the sites located in northern Iceland. In the debut competition of this series, the organizers sought design proposals for a new visitor center to be located within the Black Lava Fields of Iceland. In the second competition, which was run in partnership with Vogafj s Farm Resort, they sought ideas for a new Thermal Springs Guest House. The winning entries were selected for their respect of the sites, maintaining the landscapes’ harmony and taking advantage of the sites’ surroundings.
Keywords: Iceland; Black Lava Fields Visitors Center; Thermal Springs Guest House; landscape